Wound Healing Effects Of Ageratum Conyzoides Linn. - GOURI KUMAR DASH; P. NARASIMHA MURTHY (International Journal of Pharma and Bio Sciences, 2011)
The petroleum ether, chloroform, methanol and aqueous extracts of the leaves of Ageratum conyzoides Linn. (Asteraceae) were evaluated for their wound healing activity in rats using excision (normal and infected), incision and dead space wound models respectively. The effects of test samples on the rate of wound healing were assessed by the rate of wound closure, period of epithelialisation, wound breaking strength, weights of the granulation tissue, determination of hydroxyproline, super oxide dismutase (SOD), catalase and histopathology of the granulation tissues. Nitrofurazone (0.2% w/w) in Simple ointment I. P. was used as reference standard for the activity comparison. The results of the study revealed that the animals treated with methanol and aqueous extracts of A. conyzoides showed faster rate of wound healing compared to other extracts under study. The chloroform extract of the selected plants also produced promising results but the effects are seen to be of lesser extent than the corresponding methanol and aqueous extracts. The petroleum ether extract did not produce significant results. The present work justifies the use of the leaves ofA. conyzoides for wound healing activity as claimed in the folklore literature.